2022
DOI: 10.17219/acem/154625
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 innate lymphoid cells as an indicator of renal dysfunction and serum uric acid in hyperuricemia

Abstract: Background. Type 3 innate lymphoid cells (ILC3s) are a newly identified group of innate immune cells that participate in the progression of several metabolic diseases by secreting interleukin (IL)-17 and IL-22. These cytokines are associated with hyperuricemia (HUA) severity and development; however, the relationship between ILC3s and HUA remains unclear.Objectives. To determine the characteristics of circulating ILC3s in patients with HUA.Materials and methods. Type 3 innate lymphoid cells and their subsets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies have implicated ILC3s in various metabolic and chronic liver diseases. 21 , 33 , 34 In patients with type 2 diabetes, the frequency of peripheral ILC3s is significantly lower than that in healthy individuals, and there is a negative correlation between the levels of fasting glucose and glycated hemoglobin and the frequency of peripheral ILC3s. 34 In contrast, our previous study revealed that patients with hyperuricemia present significantly higher levels of ILC3s in PBMCs, which are positively correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have implicated ILC3s in various metabolic and chronic liver diseases. 21 , 33 , 34 In patients with type 2 diabetes, the frequency of peripheral ILC3s is significantly lower than that in healthy individuals, and there is a negative correlation between the levels of fasting glucose and glycated hemoglobin and the frequency of peripheral ILC3s. 34 In contrast, our previous study revealed that patients with hyperuricemia present significantly higher levels of ILC3s in PBMCs, which are positively correlated with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“… 34 In contrast, our previous study revealed that patients with hyperuricemia present significantly higher levels of ILC3s in PBMCs, which are positively correlated with disease severity. 33 Moreover, Wang et al observed a higher prevalence of circulating ILC3s among individuals with cirrhosis, a trend that further exacerbates as the disease advances. 21 In the present study, abnormal distribution of ILC3s was observed in human and murine MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ILC3s and IL-17A could serve as valuable indicators of disease severity and potential novel therapeutic targets for HUA. It has also been demonstrated that these ILC3 cytokines are associated with the severity and progression of HUA ( 109 ).…”
Section: Innate Lymphoid Cellsmentioning
confidence: 99%